The Role of Modernization of Information Technology in Forming the Character of the Young Hindu Generation - Ida Ayu Putu Widani Sugianingrat; I Putu Putra Astawa; Ni Wayan Wina Premayani (Universitas Warmadewa, 2024)
The development and improvement of the quality of human resources needs to be improved to keep pace with the flow of information technology modernization in the era of globalization. The phenomenon of behavior and personality tendencies of today's young generation is increasingly moving away from religious values, customs, and culture, and losing their identity as individuals which is rooted in the noble values of the nation's religion and culture. This research aims to determine the role of character education and self-leadership in forming the character of the young Hindu generation. The population in this study was the Hindu Easy Generation with a total research sample of 96 respondents. The sampling technique is probability sampling with a stratified random sampling method with proportional allocation to collect quantitative data. The research results show that character education has a positive and significant effect on the character formation of young Hindus. In the context of the formation of the character of young Hindus, self-leadership has a positive and significant effect. Thus, self-leadership plays an important role in forming the character of young Hindus who are strong and responsible while the modernization of information technology can have a positive, but not significant, effect on the formation of the character of young Hindus.